Solid pseudopapillary tumor of the pancreas: a rare entity - (:unkn) unknown (TURKISH J PEDIATRICS, 2014)
Solid pseudopapillary tumor (SPT) of the pancreas is a rare neoplasm in children that mainly occurs in young females. We herein report a rare case of SPT arising from the tail of the pancreas. A 13-year-old girl was admitted to our clinic with abdominal pain and anorexia. A mass was palpated on the physical examination. A 90x72 mm, encapsulated, heterogeneous mass with solid and cystic components was defined on computerized tomography (CT). Distal pancreatectomy was performed during the operation. Histopathological examination revealed that the tumor was a SPT with negative surgical margins. A six-month follow-up after surgical resection showed no evidence of recurrent disease. SPT should always be considered in the differential diagnosis in a young female with a palpable mass.
Keywords: solid pseudopapillary tumor; pediatric; pancreatic tumors; PEDIATRIC-PATIENTS; CHILDREN; NEOPLASMS